The Potential Short- and Long-Term Health Effects of Post-pandemic Teen Vaping - Liu, Olivia; Fan, Xiujun (International Journal of Innovative Research in Medical Science, 2023)
The COVID-19 pandemic has negatively impacted mental health throughout our society. Despite this, studies report that vaping among teens and young adults has decreased during the pandemic. This paper aims to analyze why COVID-19 impacted vaping in such a way and if that change will remain consistent as we head toward the end of the pandemic. Additionally, using PubMed and Google Scholar, we examined the different mental and physical effects of vaping and what that means for the future. Studies from the early stages of the pandemic show vaping rates among teens and young adults to be decreasing due to health concerns. However, as people become less concerned about COVID-19, vaping rates have begun to increase. The potential future health effects are unknown and need to be evaluated further.